2008
DOI: 10.1016/j.ejphar.2007.12.017
|View full text |Cite
|
Sign up to set email alerts
|

PDE4 and PDE5 regulate cyclic nucleotides relaxing effects in human umbilical arteries

Abstract: Cyclic nucleotides (cAMP and cGMP) are the main second messengers linked to vasodilatation. They are synthesized by cyclases and degraded by different types of phosphodiesterases (PDE). The effect of PDE inhibition and cyclases stimulation on 5-hydroxytryptamine (5-HT; 1 microM) and histamine (10 microM) contracted arteries was analysed. Stimulation of guanylate cyclase or adenylate cyclase relaxed the histamine- and 5-HT-induced contractions indicating that intracellular increase of cyclic nucleotides leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…Moreover, phosphodiesterase 5 activity seemed to be relevant to cGMP-linked vasodilatation 19. It is, therefore, possible that phosphodiesterase 5 inhibitor may have significant effect on hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, phosphodiesterase 5 activity seemed to be relevant to cGMP-linked vasodilatation 19. It is, therefore, possible that phosphodiesterase 5 inhibitor may have significant effect on hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cGMP plays important role in the regulation of vascular tone,18 and it has recently been reported that phosphodiesterase 5 is the key enzyme involved in the regulation of the cGMP-associated vascular relaxation 19. Therefore, hemodynamic change due to vasodilating effect of phosphodiesterase 5 inhibitor is expected.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between this artery and the systemic vessels is the lack of nerve fibers, and since it is a local physiological regulation of muscle contraction and relaxation, it is independent of nerve regulation. The vascular tonus of HUA depends entirely on vasoactive substances released locally or existing in the circulation, such as serotonin (5‐HT), histamine (His) and thromboxane, and of some ions such as calcium (Ca 2+ ) and potassium (K + ) . So, the HUA tonus is modulated by endocrine and paracrine mechanisms that regulate the contractile response of SMC .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with T0156 (1  μ M [37]) significantly increased the incorporation of EdU (140.7 ± 11.9% of the control, P < 0.05; Figure 1(a)), when compared to control cultures (no treatment). Both sildenafil and zaprinast increased EdU incorporation, in comparison to untreated cultures, as follows: sildenafil (1  μ M, 137.4 ± 7.0%, P < 0.05; 10  μ M, 120.8 ± 10.4%, P > 0.05; 50  μ M, 141.3 ± 12.6%, P < 0.01; Figure 1(b)) and zaprinast (10  μ M, 125.6 ± 7.8%, P < 0.01; 50  μ M, 118.1 ± 5.6%, P > 0.05; Figure 1(c)).…”
Section: Resultsmentioning
confidence: 99%